A Hubungan Pola Asuh Orang Tua Dengan Kemandirian Belajar Siswa Program Keahlian Tata Busana di Sekolah Menengah Kejuruan - gita fespari (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2022)
The purpose of this research is to find out; (1) the relationship between parenting and learning independence, (2) parenting applied by students' parents, (3) how much independent learning is in students. This research belongs to the type of ex-post facto research. The data collection method used a questionnaire and documentation. The data analysis technique uses descriptive analysis and hypothesis testing using the Product Moment correlation test which is preceded by normality and linearity tests. The results showed; (1) there is a positive and significant relationship between parenting styles and students' learning independence in fashion with a value of rcount = 0.722 > rtable = 0.220. The contribution given by variable X to Y is 52.1% while the remaining 47.9% is influenced by other factors not discussed in this study such as student interest in learning, facilities, parents' occupations, physical limitations, and other factors. (2) The parenting style of fashion students is in the sufficient category with a relative frequency of 59%. (3) Learning independence in fashion design students is in the high category with a relative frequency of 43%.